2015
DOI: 10.1007/s10517-015-3148-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-10 Gene Promoter Region Polymorphism in the Development of Chronic Lymphoid Leukemia

Abstract: Relationship between interleukin-10 (IL-10) gene G-1082A (rs1800896) polymorphism and the risk of development and stages of chronic lymphoid leukemia is studied in ethnic Russian residents of the Kirov region of Russia. Associations of allele -1082A and genotypes (-1082AA/-1082AG) with the risk of chronic lymphoid leukemia are detected (OR=1.39, 95%CI=1.09-1.78 and OR=1.66, 95%CI=1.09-2.54, respectively). In addition, association of 1082AA genotype with late stages of the disease by the moment of diagnosis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The details of eligible studies are presented in Table 1 . Most studies were performed in non-Chinese ethnicity, [ 13 , 17 29 ] with 4 studies in Chinese population. [ 14 , 30 – 32 ] We found that controls in 6 studies were not consistent with Hardy-Weinberg equilibrium [ 14 , 17 , 18 , 24 , 29 , 30 ] maybe because of genotyping error or selection bias during controls’ recruitment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of eligible studies are presented in Table 1 . Most studies were performed in non-Chinese ethnicity, [ 13 , 17 29 ] with 4 studies in Chinese population. [ 14 , 30 – 32 ] We found that controls in 6 studies were not consistent with Hardy-Weinberg equilibrium [ 14 , 17 , 18 , 24 , 29 , 30 ] maybe because of genotyping error or selection bias during controls’ recruitment.…”
Section: Resultsmentioning
confidence: 99%
“…SNPs in the transcriptional start area of IL-10 gene influence the production of IL-10 thus may increase or decrease the risk of cancers, [ 10 12 ] including leukemia, but the conclusions are inconsistent. For example, Ovsepyan, V. A. et al [ 13 ] found SNP in the IL-10 -1082A/G was associated with the risk of chronic lymphoid leukemia, while Lo, W. J. et al [ 14 ] found no association between IL-10 -1082A/G and leukemia. Conflicting results may be due to small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this allele may be a marker which correlates with worse prognosis, fast progression of the disease and short TFS (Lech-Maranda et al, 2013). On contrast, Ovsepyan et al shown single nucleotide replacement-1082G>A in IL-10 gene promoter region is probable genetic factor of CLL risk and of disease manifestation at advanced stages (Ovsepyan et al, 2015).…”
Section: Interleukin-10-1082a>g (Rs1800896) Single Nucleotidementioning
confidence: 97%
“…Recently, a series of epidemiological studies have focused on the association between these SNPs of IL-10 (-3575T>A, -1082A>G,-819C>T and -592C>A) and the risk of CLL (Domingo-Domènech et al, 2007;Ennas et al, 2008;Lech-Maranda et al, 2008;Lech-Maranda et al, 2013;Ovsepyan et al, 2015).…”
Section: Interleukin-10-1082a>g (Rs1800896) Single Nucleotidementioning
confidence: 99%
“…Epidemiological research studies have showed that the addition of flavonoids can reduce the risk of cardiovascular disease [4]. Ovsepyan found that macrophages secreted large amounts of C-reactive protein (CRP) and TNFα, IL-6, and other proinflammatory factors, promoting the apoptosis of smooth muscle cell and the development of atherosclerosis [5]. Coronary artery bypass surgery (CABG) has become a common cardiac surgery treatment for patients with coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%